Indications and Technique: Bipolar Patellofemoral Osteochondral Allograft Transplantation, Tibial Tubercle Osteotomy, and Medial Patellofemoral Ligament Reconstruction - José Vega MD (Video Journal of Sports Medicine, 2025)
Background: Bipolar osteochondral allograft (OCA) transplantation is a durable option for patients with symptomatic chondral defects involving the patellofemoral joint. When due to patellar instability, treatment of bipolar lesions in the patellofemoral joint requires concomitant medial patellofemoral ligament (MPFL) reconstruction (MPFLR), and often tibial tubercle osteotomy (TTO). Indications: OCA transplantation with concomitant anteromedializing TTO and MPFLR is indicated in the setting of symptomatic Outerbridge grade 3 or 4 lesions involving both the trochlea and patella due to patellar instability. Technique Description: The tibial tubercle is osteotomized at 45°. The patellofemoral joint is exposed via a laterally based arthrotomy. Fresh OCA plugs are press-fit into the trochlea and then the patella. The MPFL is reconstructed with a hamstring allograft. The lateral retinaculum is lengthened. The tibial tubercle is medialized, anteriorized, and fixed with cannulated screws. Results: We represent a 27-year-old with symptomatic bipolar chondral defects involving the patellofemoral joint due to recurrent patellar instability. Bipolar OCA transplantation to the patellofemoral joint yields significant improvements in patient-reported outcomes, and graft survival rates are high for at least 10 years after surgery. The results of bipolar OCA transplantation are improved by concomitantly correcting any underlying anatomical pathology with TTO and MPFLR, the order of which requires thoughtful consideration. Discussion/Conclusion: OCA transplantation can be safely performed in the same surgical setting as MPFLR and TTO for patients with symptomatic patellar-instability-related bipolar patellofemoral joint chondral defects. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.